2021
DOI: 10.1080/22221751.2021.1925160
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger receptor A1 participates in uptake of Leptospira interrogans serovar Autumnalis strain 56606v and inflammation in mouse macrophages

Abstract: Leptospirosis, caused by pathogenic Leptospira species, has emerged as a widespread zoonotic disease worldwide. Macrophages mediate the elimination of pathogens through phagocytosis and cytokine production. Scavenger receptor A1 (SR-A1), one of the critical receptors mediating this process, plays a complicated role in innate immunity. However, the role of SR-A1 in the immune response against pathogenic Leptospira invasion is unknown. In the present study, we found that SR-A1 is an important nonopsonic phagocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Liver macrophages are divided into two distinct populations, liver resident macrophages from the fetal yolk sac called Kupffer cells (KCs) and monocyte-derived macrophages (MDMs) from the blood. These macrophages can mediate the clearance of apoptotic cells and foreign pathogens through phagocytosis and cytokine production ( 10 ). Notably, they are also the primary regulators of the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver macrophages are divided into two distinct populations, liver resident macrophages from the fetal yolk sac called Kupffer cells (KCs) and monocyte-derived macrophages (MDMs) from the blood. These macrophages can mediate the clearance of apoptotic cells and foreign pathogens through phagocytosis and cytokine production ( 10 ). Notably, they are also the primary regulators of the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…MSR1 is mainly expressed on macrophages and dendritic cells, and recent studies have found that MSR1 is also present on the surface of lymphocytes and may be involved in the pathogenesis of asthma and chronic obstructive pulmonary disease ( 23 ). Since macrophages mediate pathogen elimination through phagocytosis and cytokine production, MSR1 expression is important for the elimination of foreign pathogens ( 10 ). LPS is an important endogenous deleterious agent, and TLR4 is the main ligand of LPS, MSR1 and TLR4 cooperation can activate phagocytosis of the Gram-negative bacterium Escherichia coli , while MSR1 interacts with TLR2 to promote phagocytosis of the Gram-negative bacterium Staphylococcus aureus ( 24 ).…”
Section: Introductionmentioning
confidence: 99%